Sistem Keamanan Ruangan Dengan Perekaman Visual Berbasis Radio Frekuensi Identification Dan Pre Hypertext Processor (PHP) di Loka Monitor Spektrum Frekuensi Radio - Yurindra Yurindra; Agusta Dirga Saputra (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2013)
The purpose of the thesis was to produce concrete results in providing security to the agencies that require special security. The method used in the manufacture of home lighting control devices based microcontroller using android smartphone is a prototype. This research method consists of several stages, library research, analytical methods, design methods, and implementation. The results achieved are ketenanagan perceived by the security agencies in masaah increased after he made these security systems. Where this tool uses a layered security system using Radio Frequency Identification (RFID) integrated with any database access. The results of testing this tool ebrhasil well where the user can sign in using RFID card and the user is not registered will be blocked and taken kgambar as evidence.